Fainting as an unusual presentation of a large inferior vena cava leiomyosarcoma. (August 2015) - Luca, Giuseppe Massimiliano De; Gurrado, Angela; Marzullo, Andrea; Piccinni, Giuseppe; Memeo, Riccardo; Vacca, Angelo; Testini, Mario
Objectives: Primary tumors of the inferior vena cava are rare, with leiomyosarcoma representing the vast majority. Method: A 60-year-old man was admitted in emergency for fainting and mild anemia. A whole-body computed tomography revealed a retroperitoneal mass of approximately 8 cm in diameter, invading the lumen of the inferior vena cava, extending to the renal vein confluence. An en bloc resection of the solid mass was performed. Macroscopically the tumor did not seem to insist on the resection margin. Results: Histopathological examination confirmed the diagnosis of leiomyosarcoma of the inferior vena cava. Postoperative recovery was uneventful and the patient was discharged after eight days, starting adjuvant chemotherapy. During the follow-up, the patient did not show other fainting episode, and at 24 months he is disease free. Conclusions: Unusually, fainting could even be the isolated sign of a large leiomyosarcoma of the inferior vena cava, also when it affects its middle portion.